On the effect of geometrical designs and failure modes in composite axial crushing: A literature review - Lau, Saijod T.W.; Said, M.R.; Yaakob, Mohd Yuhazri (2012)
Composite materials have been known for its low density, ease in fabrication, high structural rigidity, and wide range applications, i.e. aeronautic applications and automotive industry. Due to this, extensive studies had been conducted to evaluate its axial crushing ability to replace metallic materials. In this paper, it reviewed the usage of fibre reinforced plastic composite (FRP) as an energy absorption application device. Failure modes and geometrical designs such as shapes, geometry and triggering effect have been studied where these factors affected on peak load and specific energy absorption significantly. Accordingly, numerical analysis for axial crushing of affected factors had been simulated to predict the failure mechanisms of FRP composites. (C) 2011 Elsevier Ltd. All rights reserved.